Preoperative nutritional support in patients undergoing pancreatic surgery affects PREPARE score accuracy - Skalicky, Pavel; Knapkova, Katerina; Tesarikova, Jana; Gregorik, Michal; Klos, Dusan; Lovecek, Martin (Frontiers in Surgery, 2023)
Background This study aimed to validate the accuracy of the Preoperative Pancreatic Resection (PREPARE) risk score in pancreatic resection patients. Patients and methods This prospective study included 216 patients who underwent pancreatic resection between January 2015 and December 2018. All patients in our cohort with weight loss or lack of appetite received dietary advice and preoperative oral nutritional supplementation (600 kcal/day). Demographic, clinicopathological, operative, and postoperative data were collected prospectively. The PREPARE score and the predicted risk of major complications were computed for each patient. Differences in major postoperative complications were analyzed using a multivariate Cox proportional hazards regression model. The predicted and observed risks of major complications were tested using the C-statistic. Results The study included 216 patients [117 men (54.2%)] with a median age of 65.0 (30.0–83.0) years. The majority of patients were classified as American Society of Anesthesiologists (ASA)’ Physical Status score II (N = 164/216; 75.9%) and as “low risk” PREPARE score (N = 185/216; 85.6%) before the surgery. Only 4 (1.9%) patients were malnourished, with albumin levels of less than 3.5 g/dl. The most common type of pancreatic resection was a pylorus-preserving pancreaticoduodenectomy (N = 122/216; 56.5%). Major morbidity and 30-day mortality rates were 11.1% and 1.9%, respectively. The type of surgical procedure (hazard ratio [HR]: 3.849; 95% confidence interval [CI]: 1.208–12.264) and ASA score (HR: 3.089; 95% CI: 1.067–8.947) were significantly associated with the incidence of major postoperative complications in multivariate analysis. The receiver operating characteristic curve was 0.657 for incremental values and 0.559 for risk categories, indicating a weak predictive model. Conclusion The results of the present study suggest that the PREPARE risk score has low accuracy in predicting the risk of major complications in patients with consistent preoperative nutritional support. This limits the use of PREPARE risk score in future preoperative clinical routines.